Question

(b) Calculate the sum of each of the following geometric series: \( \begin{array}{ll}\text { (1) } 6+12+24+\ldots+6144 & \text { (2) } 4-8+16-\ldots+16384 \\ \text { (3) }-5+15-45+\ldots-3645 & \text { (4) } 100-10+1-\ldots+\frac{1}{10000} \\ \text { (5) } 200\left(1+(1,01)+(1,01)^{2}+\ldots+(1,01)^{28}\right) & \text { (6) }-12-6-3-\ldots-\frac{3}{256} \\ \text { (7) } x y^{2}+x y+x+\ldots+\frac{x}{y^{12}} & \text { (8) } x^{5}-x^{3}+x-\ldots+\frac{1}{x^{11}} \text { How many terms of each the following geometric series must be added to obtain the given } \\ \text { sum? } \\ \text { (1) } 2+12+72+\ldots=18662 & \text { (2) } 8+\frac{8}{3}+\frac{8}{9}+\ldots=\frac{8744}{729} \\ \text { (3) }-4+16-64+\ldots=52428 & \text { (4) } \frac{3}{4}-\frac{3}{8}+\frac{3}{16}-\ldots=\frac{513}{1024}\end{array} \

Ask by Daniel Watkins. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

Here are the simplified answers for each geometric series: 1. **Sum of \(6 + 12 + 24 + \ldots + 6144\):** - Number of terms: 11 - Sum: 12,282 2. **Sum of \(4 - 8 + 16 - \ldots + 16,384\):** - Number of terms: 13 - Sum: 10,924 3. **Sum of \(-5 + 15 - 45 + \ldots - 3,645\):** - Number of terms: 7 - Sum: -2,735 4. **Sum of \(100 - 10 + 1 - \ldots + \frac{1}{10,000}\):** - Number of terms: 7 - Sum: Approximately 90.91 5. **Sum of \(200(1 + 1.01 + 1.01^2 + \ldots + 1.01^{28})\):** - Number of terms: 29 - Sum: Approximately 6,977 6. **Sum of \(-12 - 6 - 3 - \ldots - \frac{3}{256}\):** - Number of terms: 9 - Sum: Approximately -12.00

Solution

To solve the problem, we will calculate the sum of each geometric series step by step. A geometric series can be summed using the formula: \[ S_n = a \frac{1 - r^n}{1 - r} \] where: - \( S_n \) is the sum of the first \( n \) terms, - \( a \) is the first term, - \( r \) is the common ratio, - \( n \) is the number of terms. ### (1) \( 6 + 12 + 24 + \ldots + 6144 \) - First term \( a = 6 \) - Common ratio \( r = \frac{12}{6} = 2 \) - Last term \( 6144 \) To find \( n \), we use the formula for the \( n \)-th term of a geometric series: \[ a_n = a r^{n-1} \] Setting \( a_n = 6144 \): \[ 6144 = 6 \cdot 2^{n-1} \] Dividing both sides by 6: \[ 1024 = 2^{n-1} \] Since \( 1024 = 2^{10} \), we have: \[ n - 1 = 10 \implies n = 11 \] Now, we can calculate the sum: \[ S_{11} = 6 \frac{1 - 2^{11}}{1 - 2} = 6 \frac{1 - 2048}{-1} = 6 \cdot 2047 = 12282 \] ### (2) \( 4 - 8 + 16 - \ldots + 16384 \) - First term \( a = 4 \) - Common ratio \( r = -2 \) - Last term \( 16384 \) Setting \( a_n = 16384 \): \[ 16384 = 4 \cdot (-2)^{n-1} \] Dividing both sides by 4: \[ 4096 = (-2)^{n-1} \] Since \( 4096 = 2^{12} \), we have: \[ n - 1 = 12 \implies n = 13 \] Now, we can calculate the sum: \[ S_{13} = 4 \frac{1 - (-2)^{13}}{1 - (-2)} = 4 \frac{1 + 8192}{3} = 4 \cdot \frac{8193}{3} = 10924 \] ### (3) \( -5 + 15 - 45 + \ldots - 3645 \) - First term \( a = -5 \) - Common ratio \( r = -3 \) - Last term \( -3645 \) Setting \( a_n = -3645 \): \[ -3645 = -5 \cdot (-3)^{n-1} \] Dividing both sides by -5: \[ 729 = 3^{n-1} \] Since \( 729 = 3^6 \), we have: \[ n - 1 = 6 \implies n = 7 \] Now, we can calculate the sum: \[ S_{7} = -5 \frac{1 - (-3)^{7}}{1 - (-3)} = -5 \frac{1 + 2187}{4} = -5 \cdot \frac{2188}{4} = -2735 \] ### (4) \( 100 - 10 + 1 - \ldots + \frac{1}{10000} \) - First term \( a = 100 \) - Common ratio \( r = -0.1 \) - Last term \( \frac{1}{10000} \) Setting \( a_n = \frac{1}{10000} \): \[ \frac{1}{10000} = 100 \cdot (-0.1)^{n-1} \] Dividing both sides by 100: \[ \frac{1}{1000000} = (-0.1)^{n-1} \] Since \( \frac{1}{1000000} = (-0.1)^6 \), we have: \[ n - 1 = 6 \implies n = 7 \] Now, we can calculate the sum: \[ S_{7} = 100 \frac{1 - (-0.1)^{7}}{1 - (-0.1)} = 100 \frac{1 + 0.0000001}{1.1} \approx 90.9090909 \] ### (5) \( 200(1 + (1.01) + (1.01)^{2} + \ldots + (1.01)^{28}) \) - First term \( a = 200 \) - Common ratio \( r = 1.01 \) - Number of terms \( n = 29 \) Now, we can calculate the sum: \[ S_{29} = 200 \frac{1 - (1.01)^{29}}{1 - 1.01} = 200 \frac{1 - (1.01)^{29}}{-0.01} \] Calculating \( (1.01)^{29} \): \[ (1.01)^{29} \approx 1.34885 \] Now substituting back: \[ S_{29} = 200 \cdot \frac{1 - 1.34885}{-0.01} \approx 200 \cdot \frac{-0.34885}{-0.01} \approx 6977 \] ### (6) \( -12 - 6 - 3 - \ldots - \frac{3}{256} \) - First term \( a = -12 \) - Common ratio \( r = -\frac{1}{2} \) - Last term \( -\frac{3}{256} \) Setting \( a_n = -\frac{3}{256} \): \[ -\frac{3}{256} = -12 \cdot \left(-\frac{1}{2}\right)^{n-1} \] Dividing both sides by -12: \[ \frac{1}{256} = \left(-\frac{1}{2}\right)^{n-1} \] Since \( \frac{1}{256} = \left(\frac{1}{2}\right)^{8} \), we have: \[ n - 1 = 8 \implies n = 9 \] Now, we can calculate the sum: \[ S_{9} = -12 \frac{1 - \left(-\frac{1}{2}\right)^{9}}{1 - \left(-\frac{1}{2}\right)} = -12 \frac{1 +

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

(1) The series \(6 + 12 + 24 + \ldots + 6144\) is a geometric series where the first term \(a = 6\) and the common ratio \(r = 2\). The number of terms \(n\) can be found using the formula for the nth term of a geometric series, which yields \(n = 13\). The sum \(S_n\) is calculated as \(S_n = a \frac{r^n - 1}{r - 1} = 6 \frac{2^{13} - 1}{2 - 1} = 6(8191) = 49146\). (2) The second series \(4 - 8 + 16 - \ldots + 16384\) features an alternating sign with \(a = 4\) and \(r = -2\). The number of terms can be derived in a similar fashion; here, \(n = 14\). For the sum, apply the geometric sum formula: \(S_n = 4 \frac{(-2)^{14} - 1}{-2 - 1} = 4 \frac{16384 - 1}{-3} = \frac{-65512}{-3} = 21837\). (3) For the series \(-5 + 15 - 45 + \ldots - 3645\), where \(a = -5\) and \(r = -3\), the number of terms is determined to be \(n = 8\). The sum calculated will reveal that \(S_n = -5 \frac{(-3)^8 - 1}{-3 - 1} = -5 \frac{6561 - 1}{-4} = 5(1640) = 8200\). (4) In the series \(100 - 10 + 1 - \ldots + \frac{1}{10000}\), the initial term is \(a = 100\) and the common ratio is \(-\frac{1}{10}\). Identify \(n = 5\) through analysis, leading to a sum \(S_n = 100 \frac{(-\frac{1}{10})^5 - 1}{- \frac{1}{10} - 1} = 100 \frac{-0.00001 - 1}{-1.1} = 90.9090\). (5) Explore \(200(1 + (1.01) + (1.01)^2 + \ldots + (1.01)^{28})\), with \(a = 1\) and \(r = 1.01\) leading to \(n = 29\). The sum involves using the geometric series formula: \(S_n = 200 \cdot \frac{1.01^{29} - 1}{1.01 - 1}\), approximately resulting in \(200 \cdot 298.847 = 59769.4\). (6) Analyzing \(-12 - 6 - 3 - \ldots - \frac{3}{256}\), the series where \(a = -12\) and \(r = \frac{1}{2}\) gives \(n = 9\). Here, the sum becomes \(S_n = -12 \frac{(1/2)^9 - 1}{1/2 - 1} = -12 \cdot 0.001953 - 1.7775\). (7) In the expression \(xy^2 + xy + x + \ldots + \frac{x}{y^{12}}\), one can isolate common factors leading to identification of \(a = xy^2\) and \(r = \frac{1}{y}\) with the series length \(n = 13\), summing as \(xy^2 \frac{1 - \frac{1}{y^{13}}}{1 - \frac{1}{y}} = xy^2(y^{13} - 1)/(y^{13} - y)\). (8) For \(x^5 - x^3 + x - \ldots + \frac{1}{x^{11}}\), where \(a=x^5\) and \(r = -\frac{1}{x^2}\) provides a structure to compute \(n = 12\) as it unfolds as the familiar geometric series, used to discover that each term leads toward \(x^5 \cdot \frac{1 - (-\frac{1}{x^2})^{-12}}{1 + \frac{1}{x^2}}\). So, geometry isn't just about shapes; it's about finding

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy